Synergizing Omnichannel Order Management and CRM for Competitive Advantage: A Case Study of UNIQLO’s Digital Transformation - Andartya Setyawan Darna; Muharman Lubis (Acceleration, Quantum, Information Technology and Algorithm Journal, 2025)
Intense competition in the retail industry requires companies to adopt an omnichannel strategy to create superior customer experience. This study aims to conduct an in-depth analysis of how UNIQLO, as a global retail leader, integrates Omnichannel Order Management (OOM) into its Customer Relationship Management (CRM) ecosystem. Adopting the omnichannel management framework, this study uses a qualitative case study approach based on secondary data to examine the strategies, technological enablers, and impacts of UNIQLO's "Ariake Project." The findings show that UNIQLO successfully builds a strong operational foundation through technological drivers, specifically RFID for unified inventory visibility and warehouse automation, alongside organizational drivers such as the "Takumi" culture. This integration enables flexible order fulfillment services such as Buy Online Pick-up In-Store (BOPIS), which has achieved an adoption rate of over 40%. Furthermore, the synergy with CRM has encouraged the growth of e-commerce contribution to a steady level of 15% post-pandemic. The study concludes that the key to UNIQLO's success lies in the synergistic integration of operational efficiency (OOM) and customer data intelligence (CRM), which provides actionable insights to balance technology with customer empathy in retail transformation.